RISK MANAGEMENT AND FINANCIAL REPORTING QUALITY OF ORGANISED COOPERATIVE SOCIETIES IN SOUTH-WEST, NIGERIA - Olubunmi Modupe ODUGBEMI; Muyiwa Ezekiel ALADE (Malete Journal of Accounting and Finance)
Cooperative societies have shown evidence of resilience as a result of the pooled nature of funding, this has enhanced its prominent role in financial inclusion and economic development globally. However, despite these roles, cooperative societies in Nigeria still experience challenges such as poor financial reporting quality, high loan default rate and inadequate risk management strategies. Effect of risk management on financial reporting quality of organised cooperative societies in South-west, Nigeria is examined in this research. Longitudinal research design was employed. 812 and 152 were population and sample respectively which was achieved through purposive sampling technique. Data were sourced from audited financial reports of sampled cooperative societies for twelve years (2012-2023). And analysed with aid of regression analysis techniques. The result revealed that leverage {z=0.598(p=0.004} and rate of loan default {z=0.304(p=0.044} have affirmative statistically significant effect on discretionary accrual while cash flow volatility {z=-0.0088(p=0.924} has adverse statistically insignificant effect. The study then concludes that the measures of risk management have positive statistically significant influence on financial reporting quality. In accord with the results of this research, the study then recommends that management committee of cooperative societies have to put in place strategic policies such as periodic evaluation of loan schedule to ensure members repay their loans as at when due in line with the loan contract agreement and defaulters are adequately penalise.